Visualizing biological reaction intermediates with DNA curtains. (10th March 2017) - Zhao, Yiling; Jiang, Yanzhou; Qi, Zhi
Abstract: Single-molecule approaches have tremendous potential analyzing dynamic biological reaction with heterogeneity that cannot be effectively accessed via traditional ensemble-level biochemical approaches. The approach of deoxyribonucleic acid (DNA) curtains developed by Dr Eric Greene and his research team at Columbia University is a high-throughput single-molecule technique that utilizes fluorescent imaging to visualize protein–DNA interactions directly and allows the acquisition of statistically relevant information from hundreds or even thousands of individual reactions. This review aims to summarize the past, present, and future of DNA curtains, with an emphasis on its applications to solve important biological questions.